The role of consumer awareness in rationalizing consumer ‎behavior - Yalichani, Wahiba; FarhiMohamed ‎ (Dirassat Journal Economic Issue, 2016)
This article was dictated by the urge to monitor the consumer’s behaviour. It is only an attempt to shed light on some practical ways to raise the consumer’s consciousness so the latter would be able to accomplish the real benefit, resulting from the process of consumption, by preserving his health, environment, brain, society, and national resources, in addition to protecting the consumer’s money from abuse. This is because fulfilling an unrealistic need is deemed a waste of money and an unwise behaviour. We have divided this research paper to two main parts. In that, we have began by the interactional relation between the consumer’s consciousness and his value judgment, after our explanation to the two terms: consciousness and value judgment in two separate paragraphs. Next, we have dedicated the second part to show and study the sides of consciousness accomplishing consumer’s value judgment. Thus, we have spoken about nine essential sides ( The consumer’s awareness of his real needs, his awareness of his spending limits, awareness of content displayed on the products, commercial awareness, his awareness of the exploitation means, his awareness of his rights and obligations, medical consumptive awareness, nutritive awareness, and awareness of how to deal with the rise of prices) Every side, of the early mentioned, will be explored in one paragraph among the paragraphs of the second part.